2014
DOI: 10.1017/s1047951114001255
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter closure of perimembranous ventricular septal defects with ductal occluders

Abstract: Duct occluders can be used to effectively close small- and moderate-sized ventricular septal defects. The incidence of complete heart block and valvular regurgitations are much less than reported with other devices, and they are cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Second, the Amplatzer ductal occluder device has a retention skirt only on one side as well as a long waist (7-8 mm) with a tapered configuration, which helps to hold the device firmly in place because the device stability is determined primarily by pressure gradients between the left and right chambers. 15 Third, the Amplatzer ductal occluder design enables easy manipulation, since there is no need to adjust the orientation of the device during operation. We found that the fluoroscopic time in our study was half shorter than that in a previous report when using asymmetric ventricular septal defect occluders.…”
Section: Advantages and Disadvantages In Using The Amplatzer Ductal Omentioning
confidence: 99%
“…Second, the Amplatzer ductal occluder device has a retention skirt only on one side as well as a long waist (7-8 mm) with a tapered configuration, which helps to hold the device firmly in place because the device stability is determined primarily by pressure gradients between the left and right chambers. 15 Third, the Amplatzer ductal occluder design enables easy manipulation, since there is no need to adjust the orientation of the device during operation. We found that the fluoroscopic time in our study was half shorter than that in a previous report when using asymmetric ventricular septal defect occluders.…”
Section: Advantages and Disadvantages In Using The Amplatzer Ductal Omentioning
confidence: 99%
“…Co; Ltd. China) is similar in many respects; the retention disk is 4 mm larger than the main body for smaller devices, and 6 mm for devices from 14/12 onwards. 12 The PTFE sutures are not visible on the surface of the device, allowing the use of sheaths 1F smaller in size to deliver comparable device sizes (authors' personal experience). The device, excluding the delivery system, costs approximately US $500 locally.…”
Section: The Lifetech Duct Occluder Device (Lifetech Scientific (Shenmentioning
confidence: 99%
“…Larger defects potentially can be closed using duct occluder devices with a single retention disc. To date, no study has systematically assessed the results of transcatheter closure of moderate and large sized pmVSDs using these devices . This multicenter study sought to evaluate the feasibility, safety, technical aspects, and acute results of transcatheter pmVSD closure using duct occluder devices with a single retention disc.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the proximity of VSD lesions to the conducting system as well as the aortic and tricuspid valves, special care is required while attempting closure, and a wide range of devices are now available for this procedure . The Rashkind double umbrella was the first device to be used for transcatheter closure of a perimembranous VSD.…”
Section: Introductionmentioning
confidence: 99%